Utilización del metronidazol, gentamicina y ciprofloxacino en pacientes apendicectomizados, hospitalizados en el servicio de cirugia “a” del hospital regional docente de trujillo durante el periodo mayo 2009 - mayo 2010” - Uriol Castillo, Iván Enrique (2010)
The present work of investigation is a descriptive, cross-sectional and retrospective study of the characteristics of use of Metronidazole, Gentamicin and Ciprofloxacin in the patients appendectomised of the service of surgery “A” of the Educational Regional Hospital of Trujillo during the period May 2009 - May 2010, having like universal sample to the population conformed by clinical histories of the patients committed in this service and who received treatment with the antibacterial ones before mentioned. Use Defined daily dose (DDD) for the determination of the consumption being that Gentamicina was the antibiotic of greater consumption reaching a DDD/100 bed-day of 28.56. Metronidazol (amp) is the antimicrobial that generates greater cost s. 8500.0 which represents the 78.5% of the generated total cost. One was that from the 21-30 years (31.0%) it is the age of greater prevalence for this pathology; masculine sex (57.0%) is affected and the perforated acute appendicitis (45.0%) is the frequent type